Aplication Theory Self Care of Orem and Theory Comfort of Colcaba for Postpartum Women with Caesarean Section Tubectomy - Suryani Hartati (University of Muhammadiyah Malang, 2016)
MDGs programs is to goals increase maternal health by reducing maternal mortality rate (MMR) and the increase to reproductive health for women in 2015. Therefore government made target the goals MDGs programs. Delivery by cesarean section and tubectomy are the attempts to save the state of the mother, who are in risk condition and cannot give vaginal delivery and the risky baby. Births by cesarean section can cause risk complications at 25 times than vaginal delivery, in the other hand tubectomy may cause psychosocial problem. The role of maternity nursing specialist nurse as caregiver, educator, counselor, coordinator, communicator, advocate, the agent of change and researcher is needed to reduce the occurrence of complications due to the effects of post-partum cesarean surgery and do its role in maternity nursing services to contribute on reducing the MMR. The purpose of this study was to depict focuses on the case of caesarean section and maternal postpartum tubectomy selfcare with the application of theory and the theory of comfort. The application of the theory succeeds in helping the problems experienced by the patient bio-psychosocially.